Unveiling anti-inflammatory peptides from Lion's Mane mushroom (Hericium erinaceus): Preparation, bioactivity assessment, and peptides identification - Silva B; Sringarm K; Potikanond S; Tangjaidee P; Buacheen P; Rachtanapun P; Donlao N; Singh J; Kaur L; Issara U; Kingwascharapong P; Phongthai S (Elsevier B V, 2025)
Lion's Mane mushroom (Hericium erinaceus) is acknowledged worldwide for its substantial contribution of medicinal compounds and nutrients, including protein. The efficient extraction and hydrolysis of proteins are essential for revealing their bioactive properties. This study demonstrates that the optimal pulsed electric field (PEF)-assisted extraction achieved a 42.44 % increase in protein extraction efficiency relative to traditional alkaline extraction (p < 0.05). H. erinaceus protein contained 44.59 % essential amino acids and exhibited 71.33 % in vitro digestibility. Pepsin-trypsin hydrolysis produced the most significant anti-inflammatory activity, resulting in a 36.2 % reduction in nitric oxide and a 31.8 % decrease in interleukin-6 levels (p < 0.05). Subsequent fractionations employing membrane ultrafiltration and size exclusion chromatography effectively purified the peptides, resulting in enhanced anti-inflammatory activity (p < 0.05). This research discovered nine important peptide sequences containing 50–100 % hydrophobic amino acids in Lion's Mane mushroom proteins, which could aid in the synthesis of natural anti-inflammatory peptides.
Keywords: Anti-inflammatory peptide; Alternative proteins; Lion’s Mane mushroom (Hericium erinaceus); Protein hydrolysates; In vitro digestion